Standardized preoperative corticosteroid treatment in neonates undergoing cardiac surgery: results from a randomized trial - Graham, Eric M; Atz, Andrew M; Butts, Ryan J; Baker, Nathaniel L; Zyblewski, Sinai C; Deardorff, Rachael L; DeSantis, Stacia M; Reeves, Scott T; Bradley, Scott M; Spinale, Francis G (The Journal of thoracic and cardiovascular surgery, 2011)
A heightened inflammatory response occurs after cardiac surgery. The perioperative use of glucocorticoids has been advocated as a method to improve postoperative outcomes. Randomized prospective studies to quantify the effect of methylprednisolone on perioperative outcomes in neonatal cardiac surgery have not been performed. We sought to determine whether preoperative methylprednisolone would improve postoperative recovery in neonates requiring cardiac surgery. Neonates scheduled for cardiac surgery were randomly assigned to receive either 2-dose (8 hours preoperatively and operatively, n = 39) or single-dose (operatively, n = 37) methylprednisolone (30 mg/kg per dose) in a prospective double-blind trial. The primary outcome was the incidence of low cardiac output syndrome (standardized score) or death 36 hours postoperatively. Secondary outcomes were death at 30 days, interleukin-6 levels, inotropic score, fluid balance, serum creatinine, and intensive care unit and hospital stay. Preoperative plasma levels of the inflammatory cytokine interleukin-6 were reduced by 2-fold (P < .001) in the 2-dose methylprednisolone group, consistent with the anti-inflammatory effects of methylprednisolone. However, the incidence of low cardiac output syndrome was 46% (17/37) in the single-dose and 38% (15/39) in the 2-dose methylprednisolone groups (P = .51). Two-dose methylprednisolone was associated with a higher serum creatinine (0.61 ± 0.18 mg/dL vs 0.53 ± 0.12 mg/dL, P = .03) and poorer postoperative diuresis (-96 ± 49 mL, P = .05). Inotropic requirement, duration of mechanical ventilation, intensive care unit, and hospital stay did not differ between the 2 groups. Combined preoperative and intraoperative use of glucocorticoids in neonatal cardiac surgery does not favorably affect early clinical outcomes and may exacerbate perioperative renal dysfunction.